Temple Compound and Towers of the East, Reflected in the Lakes of the Nations, California World's Fair on San Francisco Bay (Stanley A. Plitz Company)
Breath taking are the night reflections of the Towers of the East and Tower to the Sun, as reflected in the Lakes of the Nations. The facades with their bright Oriental hues and golden bas reliefs burst into augmented glory when flooded with uncolored streams of light.